The posttraumatic growth of fathers of preterm infants: protocol for a qualitative study in China - Yin, Lina; Liu, Yanli; Sunzi, Kejimu; Huang, Dandan; Huang, Jing; Tang, Liangmei; Liu, Minghui (Frontiers in Psychiatry, 2024)
Background Prematurity presents a significant life crisis for families, often exceeding their expectations. Fathers of premature infants face the burden of multiple caregiving roles and undergo psychological changes. When confronted with such crises, individuals often engage in self-evaluation and may experience positive transformations. This study aims to employ a qualitative research methodology to explore the experiences of fathers of preterm infants. Materials and methods A phenomenological approach design will be utilized, drawing upon semi-structured in-depth interviews informed by existing literature. Thematic analysis will be employed, adhering to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. In-depth individual interviews, lasting 40-60 minutes, will be conducted with fathers of preterm infants to understand their experiences. The thematic analysis process will facilitate a comprehensive understanding of the factors contributing to post-traumatic growth among these fathers. This methodology provides a structured approach to investigating the experiences and influences on post-traumatic growth in fathers of preterm infants. Results This study will highlight changes in post-traumatic growth among fathers of preterm infants. Discussion Research on the post-traumatic growth (PTG) of fathers of preterm infants is crucial to understanding the unique challenges and psychological transformations they experience. This study aims to explore the factors contributing to PTG in these fathers and how cultural contexts in China influence this process. By elucidating these aspects, the findings can inform targeted interventions and support systems tailored to the needs of fathers of preterm infants. The results may also contribute to developing guidelines and policies to promote psychological well-being and resilience among this population in the healthcare system. Ethics and dissemination This study adheres to the International Ethical Guidelines for Biomedical Research and the Declaration of Helsinki. Approval has been obtained from the People’s Hospital of Deyang Human Research Ethics Committee (No: 2019-04-150-K01). The research follows the principles of open science, and the findings will be published while ensuring participants’ confidentiality.